2014
DOI: 10.4081/jphr.2014.298
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Geographical Distribution of Enteric Protozoan Infections in Sydney, Australia

Abstract: BackgroundEnteric protozoa are associated with diarrhoeal illnesses in humans; however there are no recent studies on their epidemiology and geographical distribution in Australia. This study describes the epidemiology of enteric protozoa in the state of New South Wales and incorporates spatial analysis to describe their distribution.Design and methodsLaboratory and clinical records from four public hospitals in Sydney for 910 patients, who tested positive for enteric protozoa over the period January 2007 - De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
(71 reference statements)
5
22
0
6
Order By: Relevance
“…According to others, clinical symptoms associated with the presence of Blastocystis spp. include nausea, loss of appetite, abdominal pain or chronic diarrhea, often associated with chronic gastrointestinal disease of unknown etiology and irritable bowel syndrome (Yakoob et al, 2010;Fletcher et al, 2014). Studies conducted in Africa showed that B. hominis can be a major cause of diarrhea where poor adherence to personal and household hygiene has been described (Graczyk et al, 2005).In our study, the mean prevalence of the infection was 0.22 % in all age groups.…”
Section: Discussionsupporting
confidence: 50%
“…According to others, clinical symptoms associated with the presence of Blastocystis spp. include nausea, loss of appetite, abdominal pain or chronic diarrhea, often associated with chronic gastrointestinal disease of unknown etiology and irritable bowel syndrome (Yakoob et al, 2010;Fletcher et al, 2014). Studies conducted in Africa showed that B. hominis can be a major cause of diarrhea where poor adherence to personal and household hygiene has been described (Graczyk et al, 2005).In our study, the mean prevalence of the infection was 0.22 % in all age groups.…”
Section: Discussionsupporting
confidence: 50%
“…The highest positivity for the presence of G. intestinalis showed the youngest age category (age from 1 month to 7 years). Giardiasis more often affects infants, young children and adolescents than adults (Huston, 2006;Fletcher et al, 2014). The rapid spread of infection can take place in centres for children 12 -16 months old, or collectives (Guandalini, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms that were attributed to Blastocystis spp. include nausea, loss of appetite, abdominal pain, fl atulence, acute or chronic diarrhoea, often associated with chronic gastrointestinal disease of unknown etiology, and irritable intestine syndrome (Fletcher et al, 2014). Distribution of B. hominis is global.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance is not restricted to bacteria only. There is increasing evidence of the development of resistance among enteric protozoa from clinical samples in Australia [26][27][28].…”
Section: Antimicrobial Resistance and The Water Sanitation And Hygiementioning
confidence: 99%